CHALLENGES FACED BY INDIAN TOURISM INDUSTRY DUE THE PANDEMIC - Aqfakudeen N; Dr. J Krithika (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The tourism sector’s impact on a nation’s economic prosperity cannot be separated. The pandemic has had an impact on numerous departments, including those dealing with hotels, travel, and tourism, international trade, hospitality, and tourism management, foreign exchange, and revenue. To better understand the results of this study, data which includes turnover and profit after tax reports from the Indian Tourism Development Corporation Limited are visually displayed for five consecutive years. This study’s weakness is that the data was gathered based solely on ITDC self-reports. This study has unequivocally demonstrated that the various tourism industries have been more severely impacted by the covid epidemic. To overcome this issue and support the tourism sector, governments must act. Because it will be difficult to overcome the current issues and financial crises without government assistance. The government should either lower or do away with the taxes imposed on the travel and tourism sector.